2022
DOI: 10.1002/bsd2.218
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of state ownership in between product market competition and firm value: findings from GMM and fsQCA

Abstract: The study explores the link between product market competition (PMC) and firm value (FV) and examines the moderating role of the state ownership (SOE) variable in this relationship by using data from 555 listed firms on Vietnam's stock market from 2011 to 2019 on the Ho Chi Minh Stock Exchange (HOSE) and Ha Noi Stock Exchange (HNX). The System Generalized Method of Moments (SysGMM) is used to consider the relationship between variables. The findings from SysGMM indicate that product market competition has an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…The result of hypothesis testing suggests that market competition is negatively associated with firm value. This result is in line with Anuja and Thenmozhi (2023), Chang and Jo (2019), and Thu and Minh (2023). According to agency theory, an agency relationship is a contract between an agent and a principal in which both parties work for their interests (Jensen & Meckling, 1976).…”
Section: The Association Between Market Competition and Firm Valuesupporting
confidence: 75%
See 2 more Smart Citations
“…The result of hypothesis testing suggests that market competition is negatively associated with firm value. This result is in line with Anuja and Thenmozhi (2023), Chang and Jo (2019), and Thu and Minh (2023). According to agency theory, an agency relationship is a contract between an agent and a principal in which both parties work for their interests (Jensen & Meckling, 1976).…”
Section: The Association Between Market Competition and Firm Valuesupporting
confidence: 75%
“…Xing et al (2018) added that managers in companies with a higher competitive position could increase asymmetric information by passing price volatility to customers to reduce cash flow volatility. Anuja and Thenmozhi (2023), Jo (2019), andThu andMinh (2023) concluded that market competition is negatively associated with firm value. Companies in highly competitive markets face risks that prevent them from achieving their efforts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These combinatorial routes will provide more insight and understanding with respect to how the determinants interact and which of the determinants are more relevant, necessary, or sufficient to generate a desired firm outcome (e.g., firm performance), as shown in past business strategy development studies (Khuong & Anh, 2022;Thu & Minh, 2022). By drawing on expert fsQCA suggestions (Pappas et al, 2020) and extant empirical and theoretical discussions, we developed the configural model presented in Figure 1.…”
Section: Supply Chain Co-opetition Analytics Ambidexterity and Firm P...mentioning
confidence: 99%
“…Product market competition requires enterprises to have effective CG systems to ensure the quality of operations and provide accurate information to stakeholders (Majeed et al, 2018; Thu & Minh, 2022). Thus, when product market competition is high, CG is required to work effectively, ensuring business development and providing solutions to address competitors in the industry (De Almeida & Dalmácio, 2015; Yeh & Liao, 2020).…”
Section: Introductionmentioning
confidence: 99%